Religious Radicalism and Pluralism: The Conflict Between Religious People and Relation of Power Industry in Bekasi - Aden Rosadi (UIN Sunan Gunung Djati Bandung, 2014)
Based on category, this program leads to three social issues. First, public awareness about the significance of the view of life that is more tolerant, open and more pluralis amid development of industrialization. Industrialization that developed in centers of growth (growth poles), which prominently still holdsrural-agrarian values, has given rise to what is called the proletarian farmers.